KEIBUAN PASCAMANUSIA (POSTHUMAN) DAN EKSPLOITASI AFEKSI DALAM FILM JUNG_E - Sulastri, Euis (UI Scholars Hub, 2026)
The film JUNG_E (2023), a South Korean film by Yeon Sang-ho, presents a distinctive representation of motherhood through the transformation of the maternal body into a posthuman entity. This study aims to analyze how maternal identity is constructed, weakened, and instrumentalized through technology within the context of future capitalism and militarism. Employing a qualitative-descriptive approach, the research examines the separation of the biological body, memory, and maternal affect as they are reconstituted in the form of artificial intelligence. The theoretical framework integrates concepts of performativity and precarity/vulnerability proposed by Judith Butler, feminist posthumanism by Rosi Braidotti, affect theory by Silvan Tomkins, as well as Korean sinpa studies, to explore how maternal suffering, sacrifice, and emotional depth between mother and child are exploited through melodramatic structures and science fiction narratives. The analysis reveals that motherhood in JUNG_E is no longer positioned as an ethical relationship but rather as an affective resource that is systematically exploited. Maternal affect is programmed, commodified, and detached from the autonomy of the maternal subject, thereby exposing an ethical crisis of motherhood in the posthuman era. This study argues that JUNG_E does not celebrate posthumanism; instead, it offers a feminist critique of the exploitation of maternal bodies and emotions by technology, the state, and the logic of capitalism.